(untitled) (Trinity Journal of Management, IT & Media (TJMITM), 2010)
A financial co111ract that derives its rnlue from another asset or an index of asset values is k11ow11 as derivative. These underlying assets may be Foreign Exchange, Bonds, Equities or Commodities. For example, Forward Contracts relate to Foreign Exchange; Future to Commodities, Debt Instruments, currencies or Stock Indices; and Option to Equities. Derivatives are traded at organized exchanges and in the Over-the Counter (OTC) market.Derivatives traded at exchanges are standardized contracts having standard delivery dates and trading units. OTC derivatives are customized contracts that enable the parties to select the trading units and delivery dates to suit their requirements. Moreover, there are fewer regulatory restrictions and this facilitates innovation. A major difference between the two is that counterparty risk - the risk of default by either party; With exchange traded derivatives, the risk is controlled by exchanges through clearing houses which act as a contractual intermediary and impose margin requirements. In contrast, OTC derivatives signify greater vulnerability. Options derive their values from shares or stock market indices; an option confers the right without any obligation to buy or sell an asset at a predetermined price on or before a stipulated expiration date. Interest -rate futures are tied to debt instruments. It is a financial contract that derives its value from another asset or an index of asset values. A derivative has no physical existence but emerges out of a contract between two parties. It does not have any value of its own but its value, in tum, depends on the value of other physical assets which are called underlying assets. These underlying assets may be foreign exchange, bonds, equities or commodities. Derivatives can be thought of on the price of something. Suppose you bet with your friend on the price of a bushel of com. If the price in one year is less than 3 your friend pays you 1. If the price is more than 3 you pay your friend 1. Thus, the underlying in the agreement is the price of com and the value of the agreement to you depends on that underlying.